The Effect of Applying the Learning Cycle Learning Model on Students' Learning Outcomes of Geography - Ari Whudian; Yongha Park; Raphael Ane Atanga (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: The aims of this study were: 1) To compare the results of learning Geography of students using the Learning Cycle 7E learning model, Learning Cycle 5E with the Expository. 2) Comparing the results of learning Geography of students using the Learning Cycle 7E learning model with the Expository. 3) Comparing the results of learning Geography of students using the Learning Cycle 5E learning model with the Expository. 4) Comparing the results of learning Geography of students using the Learning Cycle 7E learning model with Learning Cycle 5E. Methodology: This study uses a Quasi-Experimental method with a "Postest-Only Control Design". The study population was students of class XI senior high school social sciences department. The samples were selected using the cluster random sampling technique, namely class XI social sciences 5, XI social sciences 7, and XI social sciences 8. Data on learning outcomes were collected through tests with description questions. Data analysis used One Way Analysis of Variance (One Way Anova) and post-ANOVA test (Scheffe' method) with a significance level of 5%. Main Findings: The results of the study showed: (1) There were differences in learning outcomes for Geography students using the Learning Cycle 7E, Learning Cycle 5E, and Expository learning models, with an average score of 73.37 : 66.55 : 58.92 respectively. The results of the one-way ANOVA test showed Fobs > Fα (25.1686 > 3.07); (2) The 7E Learning Cycle learning model produces better Geography learning achievement compared to the Expository learning model, with an average score of 73.37: 58.92; (3) The 5E Learning Cycle learning model produces better Geography learning achievement compared to the Expository learning model, with an average score of 66.55: 58.92; (4) The 7E Learning Cycle learning model produces better Geography learning achievement compared to the 5E Learning Cycle learning model, with an average score of 73.37: 66.55. The three learning models have different levels of influence, with Learning Cycle 7E having the greatest influence, followed by Learning Cycle 5E and Expository. Novelty/Originality of this study: This research has a significant contribution in the field of geography education. The results showed that the Learning Cycle 7E learning model had a more positive influence on students' Geography learning outcomes compared to the Expository learning model and the 5E Learning Cycle. These findings provide a new understanding of the effectiveness of various learning models in the context of geography education.